Dynamics and Structure of Expert Panel Examinations in Medical Malpractice Cases in the Krasnodar Krai (2010–2018) - V. A. Porоdenko; S. A. Anuprienko; N. A. Garkusha; K. A. Grigoryan; M. N. Yashchenko; G. V. Potemkin (Кубанский научный медицинский вестник, 2019)
Aim. The paper analyses the dynamics and structure of forensic medical examinations conducted by an expert panel in cases involving medical malpractice in the Krasnodar Krai (2010– 2018).Materials and methods. The authors studied the annual reports along with the archived copies of expert panel reports on the cases of medical malpractice submitted in 2010–2018 by the Department for Complex and Expert Panel Examinations (Bureau for Forensic Medical Examination, Krasnodar). The obtained results were processed using Microsoft Excel 2010 and SPSS Statistics Data Editor v.17.0. In this study, the authors employed the following methods: retrospective, comparative and analytical.Results. In 2010–2018, a total of 1,023 expert panel examinations were conducted in cases involving medical malpractice. A steady increase in the number of examinations (from 36 in 2010 to 245 in 2018) is associated with the growing number of citizens complaining about the poor quality of medical care, the interest of judicial and investigation authorities in looking into such offences, etc. A direct cause-and-effect relationship between imperfect and erroneous healthcare delivery and ensuing adverse effects was established in 212 cases, whereas indirect or no relationship was determined in 130 and 644 cases, respectively. The number of examinations pertaining to criminal cases amounted to 29.1%, showing an increase by 3.5 times (from 16 in 2010 to 57 in 2018); while the number of examinations related to civil cases and those conducted during pre-investigation checks came to 18.2% and 52.7%, respectively.Conclusion. The study shows a steady increase in the number of examinations related to medical malpractice (including criminal cases), which reveal a direct cause-and-effect relationship between errors in healthcare delivery and clinical outcomes